Construction of DesHospitaliza - Plan for responsible discharge of elderly patients with chronic diseases (Research, Society and Development, 2021)
Objective:  identify the categories that should be part of the safe discharge plan for elderly patients with chronic diseases, which will serve as a guiding document for the federal hospital units in Rio de Janeiro, aiming to contribute to the implementation of best practices in the processes of dehospitalization and transition from hospital care to primary health care. Methodology: this is an exploratory descriptive study with a qualitative approach, that uses the focus group technique and Thematic Content Analysis with IRAMUTEQ software. Results: the data analysis provided the identification of categories considered important when drawing up a safe discharge plan, which were: admission and gateway, planning for safe discharge, patient-centered care and health care education and training. Remarks: The content learned from the research indicates the need for hospital health services to develop actions, protocols and plans for safe discharge of patients. It is necessary to promote a change in organizational culture in order to advance in patient-centered care based on the integrality of care.